The Effectiveness of Microlearning in Skill Development and Knowledge Retention - Lalit Mohan Trivedi (Journal of Informatics Education and Research, 2025)
In response to the growing demand for flexible and efficient learning methods, microlearning has emerged as a popular approach, delivering content in small, digestible units, typically ranging from a few minutes to 15 minutes. This study evaluates the effectiveness of microlearning in enhancing knowledge retention and skill development, comparing it with traditional learning methods. Microlearning has gained traction in both educational and corporate settings due to its flexibility, ease of access, and ability to accommodate modern learners' busy schedules. It aligns well with the cognitive principles of minimizing cognitive overload and promoting active recall, which enhances long-term retention. Through a mixed-methods approach, this study collects data from 200 participants, including students and corporate employees, using surveys, performance assessments, and interviews. The results show that microlearning significantly improves knowledge retention, with 50.5% of participants strongly agreeing that it enhances their ability to retain information. Additionally, microlearning proves effective in skill development, with over 75% of respondents reporting improvements in job performance and the ability to apply new skills to their work. Despite its effectiveness, microlearning faces some challenges, such as the perceived lack of depth for more complex topics and limited feedback during the learning process. These findings align with concerns raised in previous literature. The study concludes that while microlearning is highly effective for knowledge retention and skill acquisition, it may need to be integrated with other learning methods for complex topics to ensure comprehensive learning outcomes. Future research should explore hybrid models to optimize microlearning's long-term effectiveness.